Waste less time on Facebook — follow Brilliant.
×

Factorise

Factorize \[(a+2b-3c)^3 +(b+2c-3a)^3+(c+2a-3b)^3\]

Note by Abhishek Alva
11 months, 2 weeks ago

No vote yet
1 vote

Comments

Sort by:

Top Newest

Let \((a+2b-3c)=x,(b+2c-3a)=y\) and \((c+2a-3b)=z.\)We can clearly see that \(x+y=z=0.\)
So,\(x^3+y^3+z^3=3(a+2b-3c)(b+2c-3a)(c+2a-3b).\) Ayush Rai · 11 months, 2 weeks ago

Log in to reply

ya your are right Abhishek Alva · 11 months, 2 weeks ago

Log in to reply

3(a+2b-3c)(b+2c-3a)(c+2a-3b) Kaustubh Miglani · 11 months, 2 weeks ago

Log in to reply

×

Problem Loading...

Note Loading...

Set Loading...